Product development strategy at basic education level - Muawanah, Nidaul; Febrianti, Aristhalia Hevi; Yuvanda, Wahyu Achmad; Zuhriyah, Indah Aminatuz (Maliki Interdisciplinary Journal, 2024)
Integrating technology into learning is an important strategy. The use of educational technology such as software development, online platforms, and educational applications provides a more interactive and in-depth learning experience for students. Additionally, the development of inclusive and adaptive teaching methods plays an important role in ensuring that all students have access to learning tailored to their needs. By offering diverse learning approaches, each individual is given the opportunity to grow and develop optimally. What is no less important is collaboration between education stakeholders, including teachers, parents, educational institutions and the community. An important aspect of developing products for primary education. This collaboration allows for the exchange of ideas, support and understanding necessary to create an inclusive and supportive educational environment. Considering these dynamic times, the development of basic education products must continue to adapt to the latest developments and student needs. Collectively, these strategies create a foundational education system that prepares students to become effective and competitive future leaders.